Pemanfaatan Limbah Kulit Pisang sebagai Alternatif Bahan Dasar Pembuatan Keripik di UMKM Lateb Jaya - Noveliska Br Sembiring; Deni Subara; Teny Sylvia; Wilda Harlia Devita (CV. Multi Kreasi Media, 2022)
Banana peel is a waste material which accounts for one-third of a whole banana that has not been peeled. Unused banana peels will certainly increase the amount of waste produced. The amount of waste will continue to increase along with the increase in banana production. One solution is to use this waste as a raw material for chips production. Besides having the potential to reduce the amount of waste, this alternative can also increase the economic value of the banana peel so that it has the opportunity to be used as a business to increase people's income